Nadzor globine anestezije z monitorjem BIS - Moller Petrun, Andreja (Zdravniški vestnik, 2010)
Background: It is difficult to measure the depth of general anaesthesia. Negative consequences might be anaesthesia awareness on the one side, a nightmare of many patients and anesthetist too, and side eff ects of too deep anesthesia on the other, which have short-term and long-term adverse effects on the patients health. This article reviews the monitoring of the depth of anesthesia with a BIS monitor, based on EEG measurements. Conclusions: BIS monitor is a clinically usefull tool for monitoring the depth of general anesthesia. With its use we can easier avoid the dangers of too shallow or toodeep anesthesia. With BISmonitor we cannot directly measure the level of analgesia. It is also important to keep in mind the factors, often present inclinical practice, which limit its usability.
Keywords: anestezija; Anestezija splošna; Anesthesia, General; Awareness; Budnost; Electroencephalography; Elektroencefalografija; Fourier Analysis; Fourierjeva analiza; Intraoperative Monitoring; nadzor